High-stability azelaic acid acne-removing emulsion and stability accelerated test evaluation method
By using the fermentation product of Sphingosine Monassia as a thickener and combining with the Turbiscan stability analyzer for parameter measurement, the problem of unpredictable stability of the formulation of high concentration water agents in azelaic acid was solved, significantly shortening the product development cycle and Ensure long-term stability of the lotion.
Patent Information
- Application Number
- CN202411550119.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
Azelaic acid is difficult to maintain stability in high concentration water agent formulations, and the existing testing methods take a long time and cannot effectively predict the long-term stability of the emulsion.
The fermentation product of Sphingosine Monassia fermentation product, which can be resistant to acid and salt at high temperatures and room temperatures, is used to measure parameters such as backscattered light change value, peak thickness, and particle migration rate, and replace traditional stability. Sexual testing method.
It significantly shortens the product development cycle, achieves a few dozen times efficiency improvement, ensures the long-term stability and effectiveness of high-concentration azelaic acid acne removal emulsion, and provides a scientific basis for formula optimization.
Smart Images

Figure CN119424232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-stability azelaic acid anti-acne emulsion and a stability accelerated test evaluation method. Background Art
[0002] Azelaic acid is a saturated straight-chain dicarboxylic acid containing nine carbon atoms, and its application value in the field of dermatology cannot be ignored. Its unique biological activities such as antibacterial, anti-inflammatory, regulating skin keratinization, inhibiting oil secretion and abnormal cell proliferation provide strong support for the treatment of skin problems such as acne and melasma, and its good safety record is also applicable to pregnant and lactating women, which further broadens its clinical application range.
[0003] However, the challenges faced by azelaic acid in the formulation process cannot be ignored. Its insolubility in water, acidic properties and strong ionicity limit its direct application in a variety of formulations. For example, the well-known 20% azelaic acid cream (Skinoren) is often criticized for problems such as precipitation and unstable quality. These problems not only affect the product experience, but also pose a challenge to its marketing and consumer acceptance. In addition, for daily chemical R&D engineers, how to screen out a suitable thickening and suspension system for high-concentration azelaic acid anti-acne lotion and other formulas with stability problems in a shorter product development cycle and ensure its long-term stability and effectiveness is also a major pain point.
[0004] In order to overcome these difficulties, researchers are constantly exploring new formulation technologies. In solving the formulation application of azelaic acid, for example, the patent with publication number CN108187070A proposes a method for preparing azelaic acid-cyclodextrin inclusion complex using cyclodextrin inclusion and spray drying technology. Although the solubility of azelaic acid has been improved to a certain extent, the complex process still needs to be further optimized, and the stability of the inclusion complex in the formula has not been explored. The patent with publication number CN117159456A prepares azelaic acid nanogel through nanotechnology. The gel reduces the amount of organic solvent while ensuring the stability and absorption effect of the sample, but the feasibility and quality control of the industrialization of nano products are difficult to achieve. The patent with publication number CN117567761B uses supramolecular technology combined with panthenol to construct a supramolecular self-recognition system that can significantly improve the water solubility and stability of azelaic acid. However, the high complexity of the technology and the specific requirements for raw materials also lead to an increase in production costs.
[0005] At present, the mainstream stability test method for opaque systems such as high-concentration azelaic acid anti-acne lotion is direct visual observation. The emulsion is placed in a sample bottle and its static stratification during storage is observed to predict the stability of the emulsion. In order to shorten the static time, the method of increasing the storage temperature is sometimes used to accelerate the stratification of the emulsion, so as to predict the storage stability of the emulsion. When the system has a stratification trend, the local concentration of the dispersed phase particles will first change. However, because the high-concentration sample is not transparent, the naked eye cannot identify the degree of increase or decrease in concentration. When the concentration change reaches the level that can be recognized by the naked eye, it often takes a long time to observe. Patent CN115774013B uses a polarized light microscope to directly analyze the cosmetic sample, and judges the stability of the cosmetic by observing the crystal precipitation of the emulsion particles. However, it only makes a judgment on the situation of crystal precipitation, and cannot predict the situation of emulsion stratification caused by changes in local particle concentration. Patent CN117016765B uses Turbiscan stability analyzer to test the stability of samples before and after freeze-thaw. The instability index TSI of each sample obtained after scanning for 12 hours is compared, which can shorten the stability inspection time. However, the TSI index alone cannot analyze the degree and process of agglomeration and stratification, and cannot provide constructive guidance for formula optimization.
[0006] In summary, the advantages of this invention are:
[0007] 1. By using the thickener Sphingomonas fermentation product, which is acid-resistant and salt-resistant at both high and room temperatures, a long-term stable high-concentration azelaic acid anti-acne lotion is obtained, solving the application problem of azelaic acid in the field of skin treatment.
[0008] 2. We invented an accelerated stability test and evaluation method for azelaic acid acne lotion with high stability. We used the Turbiscan stability analyzer for in-situ measurements and replaced traditional stability test methods with key parameters such as backscattered light change, peak thickness, and particle migration rate to compare and predict the stability of azelaic acid acne lotion. This greatly accelerated the stability test process. This technological breakthrough significantly shortened the product development cycle. Summary of the invention
[0009] The purpose of the present invention is to overcome the defect in the prior art that azelaic acid is difficult to stabilize in a high-concentration aqueous formulation, and to provide a high-stability azelaic acid anti-acne lotion. By using a thickener that is acid-resistant and salt-resistant at both high and normal temperatures, a long-term stable high-concentration azelaic acid anti-acne lotion is obtained.
[0010] Another object of the present invention is to provide a preparation process of azelaic acid anti-acne emulsion with high stability.
[0011] Another object of the present invention is to provide a stability accelerated test and evaluation method for a high-stability azelaic acid acne lotion, which uses a Turbiscan stability analyzer for in-situ measurement, and replaces traditional stability test methods with key parameters such as backscattered light change value, peak thickness, and particle migration rate to compare and predict the stability of the azelaic acid acne lotion, greatly accelerating the stability test process and achieving dozens of times of efficiency improvement. This technological breakthrough not only significantly shortens the product development cycle, but also provides a scientific basis for the formula optimization of high-concentration azelaic acid acne lotion, ensuring its long-term stability and effectiveness in clinical applications.
[0012] A technical solution to achieve the above purpose is: a high-stability azelaic acid anti-acne lotion, comprising at least the following components by weight: 1 to 20 parts of azelaic acid powder, 15 to 25 parts of propylene glycol, 0.4 to 2 parts of a thickener, and 53 to 83.6 parts of water;
[0013] The thickener is a sphingomonas fermentation product.
[0014] The above-mentioned high-stability azelaic acid anti-acne lotion includes the following components, calculated by weight: 0.6-1.2 parts of Sphingomonas fermentation product, 20 parts of azelaic acid powder, 25 parts of propylene glycol, and 53.8-54.4 parts of water.
[0015] The above-mentioned high-stability azelaic acid anti-acne lotion includes the following components in parts by weight: 20 parts of azelaic acid powder, 25 parts of propylene glycol, 0.8-1.2 parts of Sphingomonas fermentation product, and 53.8-54.2 parts of water.
[0016] In the above-mentioned high-stability azelaic acid anti-acne lotion, the mass ratio of Sphingomonas fermentation product: propylene glycol: azelaic acid is (3-6):125:100.
[0017] The above-mentioned high-stability azelaic acid anti-acne lotion, wherein the mass ratio of Sphingomonas fermentation product: propylene glycol: azelaic acid is (4-6):125:100.
[0018] The present invention also provides a method for preparing the above-mentioned high-stability azelaic acid anti-acne emulsion, comprising the following steps:
[0019] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25 to 35° C. to obtain a homogeneous concentrated solution at a stirring speed of 200 to 300 r / min to obtain phase A;
[0020] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 75-85°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0021] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 5000-7500rpm for 5-10 minutes to obtain a high-stability azelaic acid anti-acne lotion.
[0022] The present invention also provides a stability accelerated test evaluation method for the above-mentioned high-stability azelaic acid anti-acne emulsion, comprising the following steps:
[0023] S1, using Turbiscan stability analyzer to scan the samples in the sample bottle, the top peak area scanning spectrum generated during the scanning process shows the relationship between the backscattered light intensity and the height of the sample in the sample bottle, and the dynamic change of the light intensity of each group of samples under test during the measurement time is obtained. The microscopic characteristics of the top of the unstable ΔBS and the slope of the top of ΔBS over time are obtained to obtain the top light intensity change rate V1;
[0024] S2, similarly select the top peak area in the scanning spectrum to obtain the peak thickness H. The setting of the peak thickness is based on the average value of the middle backscattered light. Peaks exceeding 0.2 are judged to be effective peaks, and peaks within 0.2 are judged to be caused by other factors or noise fluctuations. The absolute value of the average value of the middle backscattered light change plus 0.2 is used as the threshold for each sample to exclude the influence of particle agglomeration. The slope of the peak thickness change over time is the particle migration rate V2;
[0025] S3, predict the stability of the system and whether it will be stratified through the two parameters of the peak thickness H and the peak height ΔBS at the top: when the two conditions of peak thickness ≥ 2mm and peak height absolute value ≥ 20% are met at the same time, the stratification phenomenon can be observed by the naked eye, but when the local concentration change reaches the level that can be recognized by the naked eye, it often takes a long time to observe. Therefore, the two parameters of peak thickness and peak height detected in the short-term measurement time and the corresponding dynamic change parameters: top light intensity change rate V1 and particle migration rate V2 are used to fit and calculate these two parameters of the sample in the long term.
[0026] ΔBS Top (T) =ΔBS top (2d) +(T-2)*V1 (2d)
[0027] HTop (T) =H Top (2d) +24*(T-2)*V2 (2d)
[0028] Where T is the time after sample preparation.
[0029] The technical solution of the high-stability azelaic acid anti-acne lotion of the present invention adopts the extract of the fermentation product of Sphingomonas as the thickener, which has excellent thermal stability, ion resistance, acid resistance and suspension ability, can improve the stability of high-concentration azelaic acid at high temperature and room temperature, and the azelaic acid concentration in the lotion formula can reach 20%.
[0030] The preparation process of the high-stability azelaic acid anti-acne emulsion of the present invention is simple and environmentally friendly, and there is a large adjustment space for adding other ingredients to the high-stability azelaic acid anti-acne emulsion.
[0031] The technical solution of the accelerated stability test and evaluation method of the high-stability azelaic acid acne-eliminating lotion of the present invention adopts a Turbiscan stability analyzer to perform efficient stability testing, and constructs a cosmetic dispersion system stability analysis and evaluation method by deriving key parameters such as backscattered light difference, peak thickness, and particle migration rate in the Turbiscan stability analyzer. The degree and process of agglomeration and stratification in the system are analyzed, and the degree of stability of the sample and the cause of instability can be characterized, replacing the method of evaluating stability by only using the TSI instability index alone. Compared with traditional stability investigation methods, the stability investigation time is greatly shortened. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The viscosity change graph of each formula at 49°C for 3 months;
[0033] Figure 2 The viscosity change graph of each formula at 25°C for 3 months;
[0034] Figure 3 The yield value change diagram of each formulation at 49°C for 3 months;
[0035] Figure 4 The yield value change diagram of each formulation at 25℃ for 3 months;
[0036] Figure 5 This is a graph showing the changes in the average light intensity of each formulation at 49°C using the Turbiscan stability analyzer. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, its specific implementation method is described in detail below with reference to the accompanying drawings.
[0038] In the following experiments, azelaic acid powder can be a general commercial raw material, and the present invention preferably uses azelaic acid powder with a purity of more than 97%. Propylene glycol can be a general commercial cosmetic raw material, and the present invention preferably uses a purity of 99.9%. The extract of Sphingomonas fermentation product comes from CP Kelco, USA. Polyacrylate cross-linked polymer-6 comes from SEPPIC, France.
[0039] Table 1, lotion ingredients formula:
[0040]
[0041] Examples 1-3 and Comparative Examples 1-5 were prepared according to the formulation in Table 1.
[0042] Embodiment 1:
[0043] A high-stability azelaic acid anti-acne lotion containing high-concentration azelaic acid comprises 1.2 parts of a sphingomonas fermentation product, 20 parts of azelaic acid powder, 25 parts of propylene glycol, and 53.8 parts of deionized water. The lotion is prepared by the following steps:
[0044] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 35°C to obtain a homogeneous concentrated solution at a stirring speed of 300 r / min to obtain phase A;
[0045] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 85°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0046] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 7500rpm for 10 minutes to obtain the high stability azelaic acid anti-acne lotion of Example 1.
[0047] Embodiment 2:
[0048] A high-stability azelaic acid anti-acne lotion containing high-concentration azelaic acid comprises 1 part of a sphingomonas fermentation product, 20 parts of azelaic acid powder, 25 parts of propylene glycol, and 54 parts of deionized water. The lotion is prepared by the following steps:
[0049] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 35°C to obtain a homogeneous concentrated solution at a stirring speed of 300 r / min to obtain phase A;
[0050] S2, pre-dispersing the thickener into the remaining propylene glycol and stirring evenly, then pouring in deionized water, continuing to stir in a high temperature 80°C water bath at a stirring speed of 400r / min until the solid particles are completely dissolved and then cooling at room temperature to obtain phase B;
[0051] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 7000rpm for 10 minutes to obtain the high stability azelaic acid anti-acne lotion of Example 2.
[0052] Embodiment 3:
[0053] A high-stability azelaic acid anti-acne lotion containing high-concentration azelaic acid comprises 0.8 parts of a sphingomonas fermentation product, 20 parts of azelaic acid powder, 25 parts of propylene glycol, and 54.2 parts of deionized water. The lotion is prepared by the following steps:
[0054] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25°C to obtain a homogeneous concentrated solution at a stirring speed of 300 r / min to obtain phase A;
[0055] S2, pre-dispersing the thickener into the remaining propylene glycol and stirring evenly, then pouring in deionized water, continuing to stir in a high temperature 80°C water bath at a stirring speed of 400r / min until the solid particles are completely dissolved and then cooling at room temperature to obtain phase B;
[0056] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 6500rpm for 10 minutes to obtain the high stability azelaic acid anti-acne lotion of Example 3.
[0057] Comparative Example 1:
[0058] A high-concentration azelaic acid anti-acne lotion comprises 0.6 parts of a sphingomonas fermentation product, 20 parts of azelaic acid, 25 parts of propylene glycol, and 54.4 parts of deionized water. The lotion is prepared by the following steps:
[0059] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25°C to obtain a homogeneous concentrated solution at a stirring speed of 300 r / min to obtain phase A;
[0060] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 75°C water bath at a speed of 300r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0061] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 6500rpm for 8 minutes to obtain the nonanedioic acid anti-acne lotion of comparative example 1.
[0062] Comparative Example 2:
[0063] A high-concentration azelaic acid anti-acne lotion comprises 1.2 parts of polyacrylate cross-polymer-6, 20 parts of azelaic acid, 25 parts of propylene glycol, and 53.8 parts of deionized water. The lotion is prepared by the following steps:
[0064] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 35°C to obtain a homogeneous concentrated solution at a stirring speed of 300 r / min to obtain phase A;
[0065] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 85°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0066] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 7500rpm for 10 minutes to obtain the nonanedioic acid anti-acne lotion of comparative example 2.
[0067] Comparative Example 3:
[0068] A high-concentration azelaic acid anti-acne lotion comprises 1 part of polyacrylate cross-polymer-6, 20 parts of azelaic acid, 25 parts of propylene glycol, and 54 parts of deionized water. The lotion is prepared by the following steps:
[0069] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 35°C to obtain a homogeneous concentrated solution at a stirring speed of 250 r / min to obtain phase A;
[0070] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 85°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0071] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 6000rpm for 10 minutes to obtain the nonanedioic acid anti-acne lotion of comparative example 3.
[0072] Comparative Example 4:
[0073] A high-concentration azelaic acid anti-acne lotion comprises 0.8 parts of polyacrylate cross-polymer-6, 20 parts of azelaic acid, 25 parts of propylene glycol, and 54.2 parts of deionized water. The lotion is prepared by the following steps:
[0074] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25°C to obtain a homogeneous concentrated solution at a stirring speed of 250 r / min to obtain phase A;
[0075] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 80°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0076] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 5000rpm for 10 minutes to obtain the nonanedioic acid anti-acne lotion of comparative example 4.
[0077] Comparative Example 5:
[0078] A high-concentration azelaic acid anti-acne lotion comprises 0.6 parts of polyacrylate cross-polymer-6, 20 parts of azelaic acid, 25 parts of propylene glycol, and 54.4 parts of deionized water. The lotion is prepared by the following steps:
[0079] S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25°C to obtain a homogeneous concentrated solution at a stirring speed of 200 r / min to obtain phase A;
[0080] S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 75°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B;
[0081] S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 5000rpm for 5 minutes to obtain the nonanedioic acid acne lotion of comparative example 5.
[0082] Test experiment 1: Appearance observation
[0083] The products of Examples 1-3 and Comparative Examples 1-5 were placed at a temperature of (25±2)°C, (49±2)°C and a relative humidity of 70%±5% for 3 months, and samples were taken for appearance observation on the 7th day, the 14th day, the 28th day, the 56th day and the 84th day. The appearance observation results are shown in Tables 2 and 3, respectively.
[0084] Table 2, 49℃ appearance changes:
[0085]
[0086] Table 3, 25℃ appearance change table:
[0087]
[0088] According to the results in Table 2, it can be seen that under the high temperature condition of 49°C, the products of Examples 1-3 have strong stability within the test period, the product of Comparative Example 1 is slightly watery, indicating the presence of precipitation, but the clear layer is very shallow and the stability is relatively general, and the products of Comparative Examples 2-5 have a clear layer visible on the top and poor stability.
[0089] According to the results in Table 3, it can be seen that under the condition of room temperature of 25°C, the products of Examples 1-3 and Comparative Examples 1-4 have strong stability within the test period, while the product of Comparative Example 5 has a clear layer on the top on the 84th day, indicating poor stability.
[0090] Test experiment 2: Viscosity test
[0091] See also Figure 1 and Figure 2 The products of Examples 1-3 and Comparative Examples 1-5 were placed at a temperature of (25±2)°C, (49±2)°C and a relative humidity of 70%±5% for 3 months to evaluate the physical stability of each formulation. Samples were taken on the 7th, 14th, 28th, 56th and 84th days to test viscosity changes.
[0092] according to Figure 1 It can be seen from the results that under the high temperature condition of 49°C, the viscosity of the high-stability azelaic acid acne lotion containing 0.6-1.2wt% of Sphingomonas fermentation product in Examples 1-3 and Comparative Example 1 did not change significantly, indicating that the microstructure of the Sphingomonas fermentation product is not sensitive to temperature changes; while in Comparative Examples 2-5, the azelaic acid acne lotion containing 0.6-1.2wt% of polyacrylate cross-linked polymer-6 experienced a significant decrease in viscosity during the 3-month stabilization process, indicating that the thickener has poor resistance to high temperatures, thereby increasing the sedimentation rate of the dispersed phase particles.
[0093] According to the attached Figure 2 It can be seen from the results that under the condition of room temperature 25°C, there is no significant difference in the viscosity of the experimental formulas of Examples 1-3 and Comparative Examples 1-5, indicating that the fermentation product of Sphingomonas, polyacrylate cross-linked polymer-6, has excellent ion resistance and acid resistance at room temperature.
[0094] Test experiment 3: Yield value test
[0095] See also Figure 3 The products of Examples 1-3 and Comparative Examples 1-5 were placed at a temperature of (25±2)°C, (49±2)°C and a relative humidity of 70%±5% for 3 months to evaluate the physical stability of each formulation. Samples were taken on the 7th, 14th, 28th, 56th and 84th days to test the change in yield value.
[0096] A Brookfield RVT Viscometer is used to measure the torque required to rotate a spindle through a liquid sample at speeds between 0.5 and 100 rpm. The torque reading is multiplied by a constant corresponding to the spindle and speed to give the apparent viscosity. The spindle speed corresponds to the shear rate. The yield value is calculated by extrapolating the measured value to a shear rate of zero. The Brookfield Yield Value (BYV) can be calculated using the following formula:
[0097]
[0098] where ηα1 and ηα2 are the apparent viscosities obtained at two different rotor speeds r1 and r2, respectively.
[0099] *Applicable only when r2 / r1=2
[0100] If using rotor speeds of 0.5 and 1 rpm:
[0101]
[0102] according to Figure 3 It can be seen from the results that under the high temperature condition of 49°C, in Examples 1-3 and Comparative Example 1, the yield value of the azelaic acid acne lotion containing 0.6-1.2wt% of the fermentation product of Sphingomonas bacteria decreased slightly, but tended to be stable after 14 days, indicating that the suspension ability of the fermentation product of Sphingomonas bacteria will not be seriously disturbed by the high temperature, so that the high concentration of azelaic acid acne lotion can also remain stable and uniform at high temperature; while in Comparative Examples 2-5, the yield value of the azelaic acid acne lotion containing 0.6-1.0wt% of polyacrylate cross-linked polymer-6 has dropped to about 10% of the initial value on the 14th day, and the azelaic acid acne lotion containing 1.2% of polyacrylate cross-linked polymer-6 has dropped to less than 20% of the initial value on the 14th day. After losing the suspension ability, the dispersed phase particles migrated rapidly, resulting in changes in the local particle concentration, and thus the phenomenon of top clearing occurred.
[0103] according to Figure 4It can be seen from the results that under the condition of room temperature 25°C, the yield value of the azelaic acid acne lotion containing 0.6-1.2wt% polyacrylate cross-linked polymer-6 in Comparative Examples 2-4 decreased slightly, but the amplitude was not large. In Examples 1-3 and Comparative Example 1, the yield value of the azelaic acid acne lotion containing 0.6-1.2wt% of the sphingomonas fermentation product did not decrease significantly. This further illustrates that the sphingomonas fermentation product, polyacrylate cross-linked polymer-6, has excellent suspension ability at room temperature.
[0104] Test experiment 4: Turbiscan multiple light scattering stability analyzer test
[0105] The Turbiscan stability analyzer uses near-infrared light (880nm wavelength) as a light source and has two synchronous dual detectors: a transmitted light detector and a backscattered light detector. The light source, the transmitted light detector and the backscattered light detector form a measuring probe. The measuring probe scans from the bottom of the sample cell to the top of the sample cell, and the completion of the measurement from the bottom to the top of the sample cell is called a scan. Over time, due to the instability of the sample, the transmitted light and the backscattered light will change, which indicates that the particle size and / or concentration or internal structure of the sample particles have changed.
[0106] A stability accelerated test evaluation method for a high-stability azelaic acid anti-acne lotion comprises the following steps:
[0107] S1, use Turbiscan stability analyzer to scan the sample in the sample bottle, the top peak area scanning spectrum generated during the scanning process shows the relationship between the backscattered light intensity and time, and the dynamic change of the light intensity of each group of samples under test during the measurement time ΔBS top and the slope of ΔBS top over time are obtained to obtain the top light intensity change rate V1. The experimental results are attached Figure 5 The overall backscattered light intensity of the samples of Examples 1-3 and Comparative Examples 1-5 has changed. Compared with the initial light intensity value, the light intensity of the azelaic acid anti-acne lotion containing 0.6-1.2wt% polyacrylate cross-linked polymer-6 has changed significantly, indicating that a certain amount of particle agglomeration has occurred.
[0108] S2, similarly select the top peak area in the scanning spectrum to obtain the peak thickness H. The setting of the peak thickness is based on the average value of the middle backscattered light. Peaks exceeding 0.2 are judged to be effective peaks, and peaks within 0.2 are judged to be caused by other factors or noise fluctuations. The absolute value of the average value of the middle backscattered light change plus 0.2 is used as the threshold for each sample to exclude the influence of particle agglomeration. The slope of the peak thickness change over time is the particle migration rate V2;
[0109] S3, the stability of the system and whether it will be stratified are predicted by the two parameters of the peak thickness H and the peak height ΔBS at the top. When the two conditions of peak thickness ≥ 2mm and peak height absolute value ≥ 20% are met at the same time, the stratification phenomenon can be observed by the naked eye. However, when the local concentration changes to a level that can be recognized by the naked eye, it often takes a long time to observe. Therefore, the two parameters of peak thickness and peak height detected in the short-term measurement time and the corresponding dynamic change parameters: top light intensity change rate V1 and particle migration rate V2 are used to fit and calculate the two parameters of the sample in the long term:
[0110] ΔBS Top (T) =ΔBS top (2d) +(T-2)*V1 (2d)
[0111] HTop (T) =H Top (2d) +24*(T-2)*V2 (2d)
[0112] Where T is the time after sample preparation.
[0113] After 2 days of high temperature testing at 49° C., the test results of the products of Examples 1-3 and Comparative Examples 1-5 using a Turbiscan multiple light scattering stability analyzer are shown in Table 4.
[0114] Table 4, Turbiscan multiple light scattering stability analyzer test results:
[0115]
[0116]
[0117] According to the results in Table 4, it can be seen that under the condition of high temperature accelerated test, from the overall trend, the fitting model can accurately capture the key change characteristics of system instability, and make a judgment consistent with the measured value on the instability degree of each group of test samples compared in the same period. In comparative examples 1-5, the azelaic acid acne lotion containing 0.6-1.2wt% polyacrylate cross-linked polymer-6 and the azelaic acid acne lotion containing 0.6wt% sphingomonas fermentation product were fitted to calculate the time of stratification observable to the naked eye to be 39.5 days, 79.83 days, 16.6 days, 14.85 days, and 15.38 days respectively; while the actual test found stratification or the time of stratification trend observable to the naked eye was: 28 days later, 56 days later, 14 days later, 14 days later, and 14 days later. The absolute value of the fitted calculation of the stratification time may deviate from the actual value by several days, mainly because the irregular properties of the dispersed phase azelaic acid particles and other factors have not been taken into account. The precision error caused by the error. From the analysis of the spectrum, the instability factor of the azelaic acid acne lotion containing 0.6-1.2wt% polyacrylate cross-linked polymer-6 is that there is a significant particle agglomeration phenomenon, which causes the particle size to increase, and the yield value decreases significantly at high temperature, indicating that the system has lost its suspension ability, and the viscosity decreases significantly, resulting in a dispersed phase particle migration rate that is much greater than that of Examples 1-3 and Comparative Example 1. Although the yield value and viscosity of the azelaic acid acne lotion containing 0.6wt% of the sphingomonas fermentation product in Comparative Example 1 do not change significantly at high temperature, since its initial values are less than those of Examples 1-3, and the particle agglomeration changes are greater than those of Examples 1-3, the phenomenon of dispersed phase particles migrating also occurs. In Examples 1-3, although the top light intensity of the azelaic acid acne lotion containing 0.8-1.2wt% of the sphingomonas fermentation product changes, the peak thickness and particle migration rate are 0, indicating that although it also has particle agglomeration, the suspension ability is not affected by high temperature, and the initial value is large enough to keep the system stable and uniform without particle migration.
[0118] In order to examine the high-temperature stability of high-concentration azelaic acid emulsion, the present invention has found through a large number of experimental studies that while monitoring the appearance and viscosity of the emulsion, it is also necessary to pay close attention to the changes in the yield value of the formula at high temperatures. People often have a misunderstanding that as long as the viscosity of the product is high enough, it can be used for suspension. In fact, higher viscosity can only slow down the movement speed of particles, and high-concentration formulas require sufficient yield value to form a stable suspension. Therefore, in addition to examining changes in appearance, viscosity, etc., this stability determination also examines changes in yield value.
[0119] The present invention uses key stability indices such as backscattered light difference, peak thickness, particle migration rate, and top light intensity change rate in the Turbiscan multiple light scattering stability analyzer to carry out detailed characterization of multiple experimental schemes in an environment of 49°C for 2 days, analyzes the degree and process of agglomeration and stratification, and compares with the traditional stability investigation method for 3 months. It is found that the conclusions obtained are consistent in the overall trend, so that engineers can make adjustments to the product stability in the early stage of the sample and reduce the uncertainty in actual observation.
[0120] In summary, the high-stability azelaic acid acne lotion of the present invention obtains a long-term stable high-concentration azelaic acid acne lotion by using a thickener, Sphingomonas fermentation product, which is acid-resistant and salt-resistant at both high and normal temperatures. The stability accelerated test evaluation method of the high-stability azelaic acid acne lotion of the present invention uses a Turbiscan stability analyzer for in-situ measurement, and replaces the traditional stability test method with key parameters such as backscattered light change value, top light intensity change rate, peak thickness, and particle migration rate to compare and predict the stability of the azelaic acid acne lotion, which greatly accelerates the stability test process and achieves dozens of times of efficiency improvement. This technological breakthrough not only significantly shortens the product development cycle, but also provides a scientific basis for the formula optimization of high-concentration azelaic acid acne lotion, ensuring its long-term stability and effectiveness in clinical applications.
[0121] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A high-stability azelaic acid anti-acne lotion, characterized in that: According to weight parts, it at least includes the following components: 1 to 20 parts of azelaic acid powder, 15 to 25 parts of propylene glycol, 0.4 to 2 parts of thickener, and 53 to 83.6 parts of water; The thickener is a sphingomonas fermentation product.
2. A high stability azelaic acid anti-acne lotion according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 20 parts of azelaic acid powder, 25 parts of propylene glycol, 0.6-1.2 parts of sphingomonas fermentation product, and 53.8-54.4 parts of water.
3. A high-stability azelaic acid anti-acne lotion according to claim 2, characterized in that: The invention comprises the following components in parts by weight: 20 parts of azelaic acid powder, 25 parts of propylene glycol, 0.8 to 1.2 parts of sphingomonas fermentation product, and 53.8 to 54.2 parts of water.
4. The high-stability azelaic acid anti-acne lotion according to claim 1, characterized in that: The mass ratio of Sphingomonas fermentation product: propylene glycol: azelaic acid is (3-6):125:
100.
5. The high-stability azelaic acid anti-acne lotion according to claim 2, characterized in that: The mass ratio of Sphingomonas fermentation product: propylene glycol: azelaic acid is (4-6):125:
100.
6. A method for preparing the high-stability azelaic acid anti-acne emulsion according to claim 1, characterized in that: The following steps are involved: S1, dispersing azelaic acid powder in propylene glycol at a mass ratio of 1:1, and stirring with a stirrer at 25 to 35° C. to obtain a homogeneous concentrated solution at a stirring speed of 200 to 300 r / min to obtain phase A; S2, pre-disperse the thickener into the remaining propylene glycol and stir evenly, then pour in deionized water, continue stirring in a high temperature 75-85°C water bath at a stirring speed of 500r / min until the solid particles are completely dissolved and then cool at room temperature to obtain phase B; S3, pour phase A into phase B, stirring while adding, the stirring speed is 500r / min, after stirring into a uniform system, homogenize at a homogenizing speed of 5000-7500rpm for 5-10 minutes to obtain a high-stability azelaic acid anti-acne lotion.
7. A stability accelerated test evaluation method for the high stability azelaic acid anti-acne lotion according to claim 1, characterized in that: The following steps are involved: S1, using Turbiscan stability analyzer to scan the samples in the sample bottle, the top peak area scanning spectrum generated during the scanning process shows the relationship between the backscattered light intensity and time, and the dynamic change of the light intensity of each group of samples under test during the measurement time ΔBS top and the slope of ΔBS top changing with time are obtained to obtain the top light intensity change rate V1; S2, similarly select the top peak area in the scanning spectrum to obtain the peak thickness H. The setting of the peak thickness is based on the average value of the middle backscattered light. Peaks exceeding 0.2 are considered to be valid peaks, and peaks within 0.2 are considered to be caused by other factors or noise fluctuations. Therefore, 0.2 is added to the absolute value of the average value of the middle backscattered light change as the threshold for each sample to exclude the influence of particle agglomeration. The slope of the peak thickness change over time is the particle migration rate V2. S3, the stability of the system and whether it will be stratified are predicted by the two parameters of the peak thickness H and the peak height ΔBS at the top: when the two conditions of peak thickness ≥ 2mm and peak height absolute value ≥ 20% are met at the same time, the stratification phenomenon can be observed by the naked eye; but when the local concentration change reaches the level that can be recognized by the naked eye, a long observation time is required; the two parameters of peak thickness and peak height detected in the short-term measurement time and the corresponding dynamic change parameters of the top light intensity change rate V1 and particle migration rate V2 are used to fit and calculate the two parameters of the sample in the long term: ΔBS Top (T) =ΔBS top (2d) +(T-2)*V1 (2d) HTop (T) =H Top (2d) +24*(T-2)*V2 (2d) Where T is the time after sample preparation.
Citation Information
Patent Citations
Method for preparing azelaic acid hydroxypropyl betacyclodextrin clathrate compound
CN108187070A
A method for analyzing the stability of cosmetics and its application
CN115774013B
A polymer emulsifier and its preparation method and application
CN117016765B
Azelaic acid nanogel as well as preparation method and application thereof
CN117159456A
A supramolecular self-recognition system that solves the application defects of azelaic acid
CN117567761B
Cited By
Method and system for monitoring thermal stability of compound emulsifier and storage medium
CN120314259A